PENGARUH POTENSIAL OSMOTIK LARUTAN EKSTRAK BAWANG MERAH TERHADAP OPTIMALISASI MUTU FISIOLOGIS BENIH KEDELAI (Glycine max L.) KULTIVAR ANJASMORO YANG TERDETERIORASI - Kadapi, Muhamad; Suminar, Erni; Na’im, Aidi (Universitas Lampung, 2025)
The longevity of soybean seed was caused to chemical compound such the protein that being easy to change by in environmental conditions during storage. Therefore, the application in increasing vigor of seed before sowing is required such as organic priming. This study aimed to determine the effect of osmotic potential treatment of shallot extract solution on the physiological quality of deteriorated soybean seeds, Anjasmoro cv based on the different osmotic potential. The research was conducted from August to September 2022 at the Seed Technology Laboratory, Faculty of Agriculture, Padjadjaran University. The experimental design used in this study was a completely randomized design (CRD) with four treatment levels of osmotic potential: 0.04 MPa (control), -0.06 MPa, -0.08 MPa, and -0.27 MPa, and four replications and duplo for each treatment. The data results were analysed using ANOVA at the 5% significance level and the post hoc analysis used the Least Significant Difference test at the 5% level of significance. The results showed significant differences in the germination rate, vigour index, growth speed, and simultaneity of growth. In contrast, there was a non-significant in the normal dry weight of seedlings among treatments. The osmotic potential treatment of shallot extract solution at -0.08 MPa affects physiological quality as shown in germination rate (75.94%), vigor index (5.87), growth speed (30.78%/ethmal), and growth simultaneity of growth (63.75%) trait. This study suggests that the osmotic potential content of shallot extract solution can optimize the physiological quality of deteriorated soybean seeds.